Penolakan Hemodialisis Pada Pasien dengan Gagal Ginjal Kronis - Santi Herlina; Fiora Ladesvita; Christine Diane (UIMA Press, 2020)
Introduction: The incidence rate of chronic kidney failure in Indonesia in 2013 was 2.0% per mil and in 2018 it increased to 3.8% per mil. Objective: The purpose of this study is to analyze the determinants of rejection of hemodialysis in Chronic Kidney Failure patients. Method: This research is a quantitative study with cross sectional approach. The population in the study were all kidney failure patients in August, amounting to 149 people. Sampling with total sampling in accordance with inclusion criteria, there were 10 patients who refused hemodialysis. Results: The results of a study with 10 patients who refused hemodialysis, 6 people (60%) covered by insurance, 5 people (50%) had kidney failure due to diabetes mellitus, 6 people (60%) patients who refused hemodialysis had poor drinking patterns, 6 people (60%) patients who reject hemodialysis have bad psychological conditions, 5 people (50%) patients who reject hemodialysis have poor family support and 6 people (60%) have poor health service support. Conclusion: The majority of hemodialysis rejection in patients with chronic kidney failure is influenced by drinking patterns, psychological conditions, family support, and poor health service support. This can be a consideration of nurses and other health teams in preparing patients and their families to make decisions according to conditions or needs of patients with chronic kidney failure. Health services can provide counseling services related to the importance of dialysis for patients with late stage chronic kidney failure, so patients choose dialysis therapy as kidney replacement therapy.